The Popularity of Pension and Unemployment Policies Revisited: The Erosion of Public Support in Britain and Germany - Ebbinghaus, B; Naumann, E (Palgrave Macmillan, 2017)
This chapter provides a comparative analysis of the long-term development of public attitudes towards pension and unemployment policies in Great Britain and Germany (1985–2013). The British and German welfare states are still rather popular. Public support for government responsibility for the elderly is stronger than for the unemployed. Moreover, a trade-off in expenditure preferences favours spending on pensions over spending on unemployment benefits. Claims toward an increased polarization between generations, union/non-union members and left/right supporters seem overblown. Welfare reforms have not led to a counter-reaction but the continued reform pressures have led to a partial erosion of public welfare state support.